Respuesta :
-4x+3y=-12
-2x+3y=-18
for this problem i want to eliminate so im going to multiply the second equaion by -2 so i can eliminate the x values and get a new equation of : 4x-6y=36
now you can eliminate
-4x+3y=-12
+ 4x-6y=36
-3y=24
y=-8
now that you have the y value so its easy to find the x, by plugging in -8 for y in either of the equations
4x+3(-8)=-12
4x-24=-12
4x=12
x=3
(3,-8)
-2x+3y=-18
for this problem i want to eliminate so im going to multiply the second equaion by -2 so i can eliminate the x values and get a new equation of : 4x-6y=36
now you can eliminate
-4x+3y=-12
+ 4x-6y=36
-3y=24
y=-8
now that you have the y value so its easy to find the x, by plugging in -8 for y in either of the equations
4x+3(-8)=-12
4x-24=-12
4x=12
x=3
(3,-8)